Maqâshid al-Qur’ân dalam Ayat Kebebasan Beragama Menurut Thahâ Jâbir al-‘Alwânî - Fawaid, Ah. (Madania: Jurnal Kajian Keislaman, 2017)
Maqâshid al-Qur’ân in the Verses of Religious Freedom in Interpretation of Thahâ Jâbir al-’Alwânî. This article is aimed at describing Thahâ Jâbir al-‘Alwânî’s interpretation on various verses dealing with the issues of religious freedom. Adapting an approach of maqâshid al-Qur’ân, the present paper comes to answer two main issues on the true of Alwânî’s maqâshid al-Qur’ân perception and the theoretical application of Alwânî’s maqâshid al-Qur’ân in interpreting verses of religious freedom. According to ‘Alwânî, it was concluded that there are three main segments that he called al-maqâshid al-Qur’âniyyah al-hâkimah: (1) al-tawhîd, (2) al-tazkiyah, and (3) al-‘umrân. ‘Alwânî stated that freedom of interfaith religion is important goal of sharia meaning. Freedom of interfaith religion, on the other hand, is one of the important embodiments in believing the God and tauhid. Seeing this pattern, the later purpose of the Quran is tazkiyah. This term is a value that enables people apply the message, fulfill the promise, and can perform the tasks of the caliphate. When such principles are implemented, something appears that Alwânî called ‘umrân as the next purpose of the Quran can be manifested well. ‘Umrân or ‘prosperity’ in which human being performs as a khalifah actually can create baldatun thayyibatun wa rabbun ghafûr as the real welfare.